Assessment of preoperative health-related quality of life in patients undergoing thyroidectomy based on patient-reported outcomes - Liu, Lei; Xiang, Yuqing; Xiong, Lujing; Li, Chao; Dai, Wei; Hu, Jinchuan; Shui, Chunyan; Zhou, Yuqiu; Wang, Xu; Ma, Linjie; Xu, Nan; Hu, Bintao; et al. (Frontiers in Psychology, 2024)
Introduction To evaluate the preoperative health-related quality of life (HRQoL) and influencing factors of HRQoL in patients undergoing thyroidectomy based on patient-reported outcomes. Materials and methods Patients who were diagnosed and treated in Sichuan Cancer Hospital from February 2022 to December 2022 and were scheduled to undergo thyroidectomy were included. Each participant completed the basic information questionnaire and patient-reported outcome assessment scales before surgery. HRQoL was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC QLQ-C30), the Thyroid Cancer-Specific Quality of Life (THYCA-QoL), and the Hamilton Anxiety Scale (HAMA). The Wilcoxon rank sum test or the Kruskal-Wallis test was used to analyze the association between patient characteristics and HRQoL, and the variables with statistical significance were included in multiple linear regression analysis. Results 450 patients were included in the study. According to the analysis of the THYCA-QoL scores, the psychological subscale was the most complained about. Anxiety was the most common symptom of the HAMA. Factors associated with worse general QoL on the EORTC QLQ-C30 included nondiagnostic/unsatisfactory fine-needle aspiration (FNA) result. Planned lateral neck dissection and nondiagnostic/unsatisfactory FNA result were influential factors for preoperative anxiety. Males and longer sleep duration were associated with better thyroid cancer-specific QoL, better general QoL, and less anxiety. Conclusion The preoperative HRQoL of patients undergoing thyroidectomy was generally good. Females, insufficient sleep duration, planned lateral neck dissection, and nondiagnostic/unsatisfactory FNA result were associated with worse preoperative HRQoL.